2021
DOI: 10.1084/jem.20200303
|View full text |Cite
|
Sign up to set email alerts
|

IFITM3 incorporation sensitizes influenza A virus to antibody-mediated neutralization

Abstract: The disease severity of influenza is highly variable in humans, and one genetic determinant behind these differences is the IFITM3 gene. As an effector of the interferon response, IFITM3 potently blocks cytosolic entry of influenza A virus (IAV). Here, we reveal a novel level of inhibition by IFITM3 in vivo: We show that incorporation of IFITM3 into IAV particles competes with incorporation of viral hemagglutinin (HA). Decreased virion HA levels did not reduce infectivity, suggesting that high HA density on IA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Others have also reported that IFITM1 and IFITM3 have a different tissue-specific expression pattern during H9N2 infection in BALB/c mice (Yu and others 2015 ). Moreover, IFITM3 preferentially localizes in both early and late endosomes and lysosomal structures, so it can counteract the invading viruses more effectively and during more extended periods than IFITM1 (Lanz and others 2021 ). Furthermore, it has also been documented that besides preventing influenza A virus (IAV) fusion with the endosomal membrane, IFITM3 can also incorporate into IAV particles competing with viral hemagglutinin incorporation, therefore sensitizing the virus to antibody neutralization, and thus having an impact on the infection outcome (Lanz and others 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Others have also reported that IFITM1 and IFITM3 have a different tissue-specific expression pattern during H9N2 infection in BALB/c mice (Yu and others 2015 ). Moreover, IFITM3 preferentially localizes in both early and late endosomes and lysosomal structures, so it can counteract the invading viruses more effectively and during more extended periods than IFITM1 (Lanz and others 2021 ). Furthermore, it has also been documented that besides preventing influenza A virus (IAV) fusion with the endosomal membrane, IFITM3 can also incorporate into IAV particles competing with viral hemagglutinin incorporation, therefore sensitizing the virus to antibody neutralization, and thus having an impact on the infection outcome (Lanz and others 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Negative imprinting might reasonably occur through a similar mechanism to how IFITMs disrupt virus–cell membrane fusion in target cells, that is, via altering virus membrane properties. One study noted that IFITM3 expression displaced IAV HA from viral particles, which in turn sensitized the virus to neutralizing antibodies ( 68 ). At present, it is unclear whether this mechanism involves direct binding between IFITMs and HA ( 63 ) or if it will be applicable to other viruses.…”
Section: The Role Of Ifitms In Viral Infectionmentioning
confidence: 99%
“…The plasmids encoding HA and NA of strain A/WSN/33 in the backbone of the pCAGGS vector have been described before ( 36 , 37 ). To express wild-type or catalytically inactive CTSW (CTSW WT and CTSW mut, respectively), the constructs pLVX-CTSW(WT, siRes#2)-IRES puro and pLVX-CTSW(C153A, siRes#2)-IRES puro were used ( 5 ).…”
Section: Methodsmentioning
confidence: 99%